Efficacy and Safety of Empagliflozin in the Management of Diabetes Mellitus in Heart Transplant Recipients. Issue 5 (May 2019) - Cehic, Matthew G.; Muir, Christopher A.; Greenfield, Jerry R.; Hayward, Christopher; Jabbour, Andrew; Keogh, Anne; Kotlyar, Eugene; Muthiah, Kavitha; Macdonald, Peter S.
Abstract : Background: Type 2 diabetes mellitus (T2DM) is prevalent in patients undergoing heart transplant, and in those without preexisting T2DM, posttransplant diabetes mellitus may develop. Both T2DM and posttransplant diabetes mellitus have been associated with increased morbidity and mortality following heart transplantation. Empagliflozin is an effective glucose-lowering therapy that reduces the incidence of major cardiovascular events in patients with T2DM. The safety and efficacy of empagliflozin in transplant patients with diabetes mellitus has yet to be established. Methods: Clinical outcomes were retrospectively examined in 22 heart transplant recipients treated with empagliflozin and compared with those of 79 heart transplant patients with diabetes mellitus receiving alternative glucose-lowering therapies. Results: Three adverse events were recorded in empagliflozin-treated patients, leading to treatment discontinuation in 1. There were no genitourinary infections. Treatment with empagliflozin for 12 months was associated with reductions in weight, body mass index, glycated hemoglobin, and frusemide dose that were not seen in the control group. There were no large changes observed in blood pressure (systolic or diastolic) or renal function (serum urea, creatinine, or estimated glomerular filtration rate) after 12 months of treatment with empagliflozin or alternative glucose-lowering therapies. Conclusions: Empagliflozin appears safe and effective in the management of selected patients with diabetes mellitus following heart transplantation.